Achieving consensus and controversy around applicability of palliative care to dementia. (10th June 2015) - van der Steen, Jenny T.; Radbruch, Lukas; de Boer, Marike E.; Jünger, Saskia; Hughes, Julian C.; Larkin, Phil; Gove, Dianne; Francke, Anneke L.; Koopmans, Raymond T.C.M.; Firth, Pam; Volicer, Ladislav; Hertogh, Cees M.P.M.
ABSTRACT: Background: People with dementia may benefit from palliative care which specifically addresses the needs of patients and families affected by this life-limiting disease. On behalf of the European Association for Palliative Care (EAPC), we recently performed a Delphi study to define domains for palliative care in dementia and to provide recommendations for optimal care. An international panel of experts in palliative care, dementia care or both, achieved consensus on almost all domains and recommendations, but the domain concerning the applicability of palliative care to dementia required revision. Methods: To examine in detail, the opinions of the international panel of 64 experts around the applicability of palliative care, we explored feedback they provided in the Delphi process. To examine which experts found it less important or less applicable, ordinal regression analyses related characteristics of the panelists to ratings of overall importance of the applicability domain, and to agreement with the domain's four recommendations. Results: Some experts expressed concerns about bringing up end-of-life issues prematurely and about relabeling dementia care as palliative care. Multivariable analyses with the two outcomes of importance and agreement with applicability indicated that younger or less experienced experts and those whose expertise was predominantly in dementia care found palliative care in dementia less important and less applicable. Conclusions: Benefits of palliative care in dementia are acknowledged by experts worldwide, but there is some controversy around its early introduction. Further studies should weigh concerns expressed around care receiving a "palliative" label versus the benefits of applying palliative care early.